The effects of straw return on potassium fertilization rate and time in the rice-wheat rotation - Zhao, Xinlin; Wang, Huoyan; Lu, Dianjun; Chen, Xiaoqin; Zhou, Jianmin (Soil science and plant nutrition (Tokyo), 2019)
In order to investigate the effects of straw return on potassium (K) fertilizer application rate and time in the rice-wheat rotation, field experiments were conducted at three sites. The results showed that when the K rate was decreased to 70% of the recommended K dosage, crop yields showed no significant decrease. With K fertilization only at rice phase, crop yields showed no marked difference compared with that provided K fertilizer both at wheat and rice seasons. Though the NH 4 OAc-extracted K and HNO 3 -extracted K differed slightly among the treatments, the soil apparent K balance was negative without K fertilization. With crop straw fully incorporated, the recommended K dosage could be at least reduced by 30% at the experimental sites and the K fertilizer could be applied only at rice phase. A further hypothesis can be made that the best K rate was the amount of K took away by crop grain. In the long run, straw return combined with K fertilization would be an effective method to maintain soil K fertility and productivity.